Starting and managing a nonprofit organization : a legal guide - Hopkins, Bruce R. (New York : Wiley, 2012)
Nuts-and-bolts guidance on the laws, rules, and regulations governing the nonprofit sector-from leading nonprofit law expert, Bruce R. Hopkins Nonprofits must comply with stringent federal and state laws due to their special tax-exempt status; the government's ultimate threat is revocation of a nonprofit's tax-exempt status, which usually means the nonprofit's demise. Written in plain English, not ""legalese, "" Starting and Managing a Nonprofit Organization: A Legal Guide, Sixth Edition, provides essential guidance for those interested in starting nonprofits, as well as valuabl.
Preface -- Acknowledgments -- Starting a nonprofit organization -- What is a nonprofit organization? -- Starting a nonprofit organization -- Debunking some myths and misperceptions -- Being nonprofit, legally -- Nonprofit organizations : much more than charity -- Glossary -- Index.
Includes index.
Print version record.
Keywords: Nonprofit organizations -- Law and legislation -- United States; Nonprofit organizations -- Taxation -- Law and legislation -- United States; Nonprofit organizations -- Law and legislation; Nonprofit organizations -- Taxation -- Law and legislation; United States; Electronic books